The Arabidopsis SR45 Splicing Factor, a Negative Regulator of Sugar Signaling, Modulates SNF1-Related Protein Kinase 1 Stability - Carvalho, Raquel F. (2018)
The deposited article is a post-print version and has been submitted to peer review.